Inhibition of platin-induced BCL2 increase overcomes chemoresistance in squamous cell carcinoma of the head and neck through resensitization to cell death - Anne-Sophie Becker; Friederike Klauk; Thomas Freitag; Daniel Fabian Strüder; Björn Schneider; Annette Zimpfer; Claudia Maletzki (Translational Oncology)
The clinical outcome of head and neck squamous cell carcinoma (HNSCC) remains poor with high recurrence rates, in part due to resistance to concurrent platinum-based chemotherapy. The anti-apoptotic BCL2 protein is involved in apoptosis resistance and tumor cell invasion/migration. Here, we test whether BCL2 overexpression predicts poor therapeutic response of HNSCC to cisplatin-based chemoradiotherapy and the effects of selective BCL2 inhibition on cisplatin-induced cell changes in vitro.BCL2 immunostatus was correlated with survival after chemoradiotherapy in a uniformly treated HNSCC cohort. The combination therapy of ABT-199, a BCL2 inhibitor, and cisplatin was evaluated in vitro using corresponding patient-derived cell lines. Colony formation and the mode of cell death were analyzed in-depth.Patients with BCL2-positive tumors (44/254) prior to treatment (either radiation, cisplatin monotherapy, or both) had shorter overall and progression-free survival (log-rank; p = 0.048) and a higher rate of tumor relapse (Fisher's exact test; p = 0.0032). BCL2 inhibition alone had no effect on cell functions in our triple panel of cisplatin-sensitive cell lines but enhanced cisplatin-induced effects. Rates of autophagy and cell death, including methuosis, were doubled, while epithelial-mesenchymal transformation was inhibited.As selective inhibition of BCL2 is available and standard of care in other malignancies, its immunohistochemical assessment could help personalize therapy by identifying a subpopulation to overcome chemoresistance, particularly in locally advanced HNSCC.